2008
DOI: 10.1007/s12072-008-9066-1
|View full text |Cite
|
Sign up to set email alerts
|

Current therapy for hepatitis C or D or immunodeficiency virus concurrent infection with chronic hepatitis B

Rong-Nan Chien

Abstract: Concurrent hepatitis C virus (HCV), hepatitis delta virus (HDV), or human immunodeficiency virus (HIV) infection with chronic hepatitis B virus (HBV) appears to increase the risk of progressive liver disease including liver cirrhosis and hepatocellular carcinoma. There is a 10% prevalence of HCV infection in chronic HBV or HDV infection. Serological evidence of previous exposure to HBV is found in more than 80% of HIVpositive patients in the high risk group. Notably, the most recently acquired virus tends to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
7
1
1
Order By: Relevance
“…Therefore, concurrent infection with these viruses may occur and complicate the natural course of chronic HBV infection. In general, concurrent infection with these viruses usually results in more severe and progressive liver disease and thus needs treatment [39].…”
Section: Concurrent Infection With Other Virus(es)mentioning
confidence: 99%
“…Therefore, concurrent infection with these viruses may occur and complicate the natural course of chronic HBV infection. In general, concurrent infection with these viruses usually results in more severe and progressive liver disease and thus needs treatment [39].…”
Section: Concurrent Infection With Other Virus(es)mentioning
confidence: 99%
“…Meanwhile, studies comparing IFN plus lamivudine combination therapy with IFN monotherapy found similar therapeutic effects 8,22,104 and similar persistent benefits. 96,105,106 IFN in combination with adefovir was likewise found to have roughly the same therapeutic effect six months after treatment as IFN alone. 107 It has been reported that Peg-IFN in combination with entecavir or adefovir produces better negative conversion of HBsAg and reduction in cccDNA levels.…”
Section: Should Nas Be Administered At the Same Time?mentioning
confidence: 82%
“…IFN administered in combination with lamivudine produces improved HBV DNA negative conversion and ALT normalization outcomes compared to lamivudine alone, for both HBeAg positive and negative patients. Meanwhile, studies comparing IFN plus lamivudine combination therapy with IFN monotherapy found similar therapeutic effects and similar persistent benefits . IFN in combination with adefovir was likewise found to have roughly the same therapeutic effect six months after treatment as IFN alone .…”
Section: Pharmacotherapy (1) – Ifnmentioning
confidence: 87%
“…Earlier studies showed that HBV genotypes A and B had a better response to IFN and PEG IFN treatment than genotypes D and C, respectively [57]. Patients with genotype C had a lower response than those with genotype B when treated with a lower dosage of PEG IFN-α 2a (90 μg) or for a shorter duration (24 weeks) [52].…”
Section: Treatment With Peg Ifn-αmentioning
confidence: 99%